Pemahaman Dan Penguasaan Model-Model Komunikasi (Studi Empiris Terhadap Mahasiswa Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Pattimura) - Olivia Tahalele; Fatima Suatrat; Sandra Ivonnie Telussa; Johana Nahuway; Haryati Haryati; Andi Muh Akbar Saputra (Departement of Mathematics Education, 2023)
The communication model is a simple description of what is needed for communication to occur by abstractly representing its important characteristics and eliminating irrelevant details. This study examines the understanding and mastery of communication models by students of the Communication Science Study Program, Faculty of Social and Political Sciences, Pattimura University. The research was conducted using a quantitative method with a sample size of 30 respondents. The research data consisted of primary and secondary data collected through literature study, observation, structured interviews, and student evaluations. The data were analyzed quantitatively using a descriptive percentage analysis. The results showed that overall, the average achievement of understanding and mastery of communication models by most students was 80%, with only a small percentage of students still lacking understanding and mastery (14%) and a minority who did not understand and master the models (6%). This finding provides valuable input for strengthening the learning process of communication models in lectures and serves as a collective consideration for further actions that should be implemented by course instructors in order to maximize the understanding and mastery of communication models among students of the Communication Science Study Program, Faculty of Social and Political Sciences, Pattimura University.